Mesoscale surface circulation and variability of Southern Indian Ocean derived by combining satellite altimetry and drifter observations - Benny, N. Peter (Springer Verlag, 2015)
High resoultion Eulerian mean velocity field has been derived by combining the satellite tracked surface drifter data with satellite altimetry and ocean surface winds. The drifter data used in this study includes Argos and surface drifter data from Global Drifter Program. Maps of Sea Level Anomaly (MSLA) weekly files with a resolution of (1/3)° in both Latitude and Longitude for the period 1993–2012 have been used. The Ekman current is computed using ocean surface mean wind fields from scatterometers onboard ERS 1/2, Quikscat and ASCAT. The derived mean velocity field exhibits the broad flow of Antarctic Circumpolar Current with speeds up to 0.6 m/s. Anomalous field is quite significant in the western part between 20° and 40°E and in the eastern part between 80°E and 100°E with velocity anomaly up to 0.3 m/s. The estimated mean flow pattern well agrees with the dynamic topography derived from in-situ observations. Also, the derived velocity field is consistent with the in-situ ADCP current measurements. Eddy kinetic energy illustrates an increasing trend during 1993–2008 and is in phase coherence with the Southern Annular Mode by three month lag. Periodic modulations are found in the eddy kinetic energy due the low frequency Antarctic Circumpolar Wave propagation.